Optimization of Enterprise Resource Planning (ERP) Applications on The Crew Contract Extension System At PT. Sinarmas LDA Maritime - Prasetiawan, Andi; Widiatmaja, Arya; Megawanti, Rima (RSF Conference Series: Engineering and Technology, 2023)
Technological developments are needed in today's digital era because they can help all human activities. PT. Sinarmas LDA Maritime created an Enterprise Resource Planning (ERP) application. The ERP application is used to simplify employees' work in inputting data and monitoring the working period of the crew and the validity period of documents. However, in using the ERP application, there are obstacles to the crew contract extension system, which still uses paper forms, so inputting data into the application takes a long time. Besides that, the ERP application is very dependent on the internet network. This study aims to determine the constraints in optimizing Enterprise Resource Planning (ERP) applications on the crew contract extension system with the addition of problem solvers. This research method uses a qualitative description approach by conducting observations, interviews, literature studies, and documentation directed at competent and directly involved informants and using SWOT analysis techniques to determine strategic factors for optimizing Enterprise Resource Planning (ERP) applications by linking research data results. Based on the research that has been done, it was found that optimizing the Enterprise Resource Planning (ERP) application in the crew contract extension system is filling in crew data that still uses paper forms and is dependent on the internet network. Using a paper form is changed to using a G-form so that the input of crew data for extended counters is more effective and efficient. As well as the need for outreach to the ship's crew in order to know the stages of filling in the data. The results of the SWOT analysis show that the Enterprise Resource Planning (ERP) application is in a progressive strategy position, meaning that obstacles in optimizing ERP applications can be overcome because the company is able to take advantage of its strengths and opportunities.